Small Wind Turbines Analysis, Design, and Application - Wood, David (2011)
Small Wind Turbines provides a thorough grounding in analysing, designing, building, and installing a small wind turbine. Small turbines are introduced by emphasising their differences from large ones and nearly all the analysis and design examples refer to small turbines. The accompanying software includes MATLAB® programs for power production and starting performance, as well as programs for detailed multi-objective optimisation of blade design. A spreadsheet is also given to help readers apply the simple load model of the IEC standard for small wind turbine safety. Small Wind Turbines represents the distilled outcome of over twenty years experience in fundamental research, design and installation, and field testing of small wind turbines. Small Wind Turbines is a suitable reference for student projects and detailed design studies, and also provides important background material for engineers and others using small wind turbines for remote power and distributed generation applications.
1. Introduction to Wind Turbine Technology -- 2. Control Volume Analysis for Wind Turbines -- 3. Blade Element Theory for Wind Turbines -- 4. Aerofoils: Lift, Drag, and Circulation -- 5. Blade Element Calculations -- 6. Starting and Low Wind Speed Performance -- 7. Blade Design, Manufacture, and Testing -- 8. The Unsteady Aerodynamics of Turbine Yaw and Over-speed Protection -- 9. Using the IEC Simple Load Model for Small Wind Turbines -- 10. Tower Design and Manufacture -- 11. Generator and Electrical System -- 12. Site Assessment and Installation.
Keywords: Engineering; PRODUCTION OF ELECTRIC ENERGY OR POWER; RENEWABLE ENERGY SOURCES; HYDRAULIC ENGINEERING; ENGINEERING FLUID DYNAMICS; MACHINERY AND MACHINE ELEMENTS; RENEWABLE AND GREEN ENERGY; POWER ELECTRONICS, ELECTRICAL MACHINES AND NETWORKS